Pharmacokinetics and pharmacodynamics of oral and intravenous metoprolol tartrate in clinically healthy horses. Issue 2 (15th December 2021) - Luethy, Daniela; Robinson, Mary A.; Stefanovski, Darko; Haughan, Joanne; Torcivia, Catherine; Kowalski, Alycia; Ford, Matthew; You, Youwen; Missanelli, Jaclyn; Slack, Joann
Abstract: Cardiac drugs with defined pharmacological parameters in horses are limited. The objective of this study was to characterize the pharmacokinetic properties and cardiovascular effects of intravenous and oral metoprolol tartrate (MET) in horses. In a 2‐period randomized cross‐over design, MET was administered IV (0.04 mg/kg) and PO (6 mg/kg) once to six healthy adult horses. Horses were monitored via continuous telemetry and non‐invasive blood pressure (NIBP). Blood samples were serially collected for 72 h post‐administration, and concentrations were determined by LC‐MS/MS. Pharmacokinetics were modeled using a 3‐compartment model and non‐linear least squares regression. Median (range) MET concentration was 110 (40.1–197) ng/ml collected 1 min (0.0167 h) after a bolus IV administration. Maximum concentration ( C max ) after PO administration was 2135 (1590–4170) ng/ml at 0.5 (0.25–0.5) hours. Oral bioavailability was 54% (17–100%). Median apparent volume of distribution was 0.39 (0.17–0.58) l/kg, clearance was 12.63 (11.41–18.94) ml/kg/min, and elimination half‐life was 21.1 (7.46–34.36) minutes. No clinically relevant effects of IV or PO metoprolol were noted on cardiac rhythm or NIBP. Sweating was the most common side effect. The metoprolol doses used in this study achieve plasma concentrations reported to achieve ß‐blockade in humans.